Gospodarne konstrukcije v lesu - Juvanec, Borut (Les (Ljubljana), 1999)
Architecture developed from that trade, which assures the human protecting from outer influences: from dead and from live nature. With use of tools he assured himself more resources as he needed for the bare survival - he had theopportunitiy to use his energy somewhere else. The same developed the art. Architecture is something in between art of forming space and technics. Architecture is whole bunch of consumer?s requests, posibillity of nature and of course ability of builder. At that the nature is quite generous, but one must have knowingness and willingness to make good use of it. The most important elements are usage of sun energy, regulation of constant moisture at lower temperatures and regulation of even higher warmth in buildings. HAYRACK is the best example of the first rule: it is located with it?s roof facing perpendicularly to the sun rays. It is located in the direction of the wind blowing where the efficiency of the wind is the greatest. Hayrack is the most clever building (in it?s function), what we received from our grandfathers. CELLAR is the element of the building, which supports the construction, and at the same time exploitates the lower temeratures of the soil and soil moisteness for keeping it?s contents. GRANARY is composed from stone-made wall or bricked wall cellar and wooden body. It exploites soil for lower temperature and good moistness, and in it?s upper part for warmth of outer space. SELF SUPPORTIVE CONSTRUCTION pooling the characteristics of granary in wood with clever construction, which meaning at the same time circumference and load capacity, and at the same time saves the material, work and in the last phase keeps the nature, quite a lot trees, which would carry the construction and from that reason can stand. Trees keeps the nature eqilibrum, cleans the air and it?s beautiful too. Architecture has three elements: function, construction and decoration. When all of three elements are interweaved the most, when works in it?s fulness, then the architecture is perfect. Today we can regulate the activity. For that we needs enormous quantity of energy. that is very costly. Cheap solutions, which nature offers us, are not cheap, they are for free. One must just see it. And knows how to build in. Our predecesors knows that.
Keywords: lesene konstrukcije; kozolci; kleti; kašče; lastnosti